Study of Antimicrobial Sensitivity Pattern of Bacterial Pathogens Causing Urinary Tract Infections at a Tertiary Care Hospital (Jalalabad Medical Journal, 2026)
Urinary tract infection (UTI) is one of the most common bacterial infection in outpatients and hospitalised patients in Bangladesh. This cross-sectional study was carried out in Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, during the period of October 2023 to April 2024. The aim of the study was to determine the antibiotic sensitivity pattern among uropathogens causing UTI. Clinically diagnosed cases of UTI from the outpatient department and inpatient department were selected for the study purpose. Urine was collected from symptomatic UTI cases attending the hospital and processed in the microbiology lab. A total of 3050 urine samples were analysed. Among the total number, 400 urine samples were culture positive. The most common organisms isolated were Escherichia coli (68.8%), Klebsiella (30.2%) and Pseudomonas (1%). More than 90% of the isolates were sensitive to nitrofurantoin, while more than 80% were sensitive to meropenem, netilmicin and piperacillin-tazobactam. Very high rates of resistance were seen against cefixime (78%), azithromycin (77.8%), cefepime (74.8%) and cefuroxime (74.8%). Escherichia coli showed high sensitivity to nitrofurantoin (94.2%) and meropenem (89.8%) with good sensitivity to fosfomycin (86.2%), piperacillin-tazobactam (84.7%), netilmicin (84%) and amikacin (80%). Klebsiella was highly sensitive to nitrofurantoin (89.2%), meropenem (86.8%), fosfomycin (83.5%), netilmicin (83.5%), piperacillin-tazobactam (82.6%) and amikacin (75.2%). Pseudomonas was 100% sensitive to nitrofurantoin, meropenem, netilmicin, amikacin and piperacillin-tazobactam. Females of reproductive age groups are vulnerable to developing UTIs. E. coli and Klebsiella are two common pathogens causing UTIs. Nitrofurantoin and meropenem are highly sensitive, and cephalosporins and azithromycin are highly resistant to these organisms.Jalalabad Med J 2025; 22 (2): 84-88